Zinc-based amendments and Zn-solubilizing beneficial bacteria mitigate lead-induced toxicity in chickpea (Cicer arietinum L.) - Shahid, Mohammad; Farah, Mohammad Abul; Al-Anazi, Khalid Mashay; Koolman, Leonard (Frontiers in Microbiology, 2025)
Lead (Pb) is a toxic metal that disrupts plant physiological processes and poses significant human health risks. Fertilizers, nanomaterials, and mineral-solubilizing plant growth-promoting rhizobacteria (PGPR) support phytoremediation as an emerging, eco-friendly strategy for metal detoxification by improving nutrient availability and minimizing metal toxicity in plants. This study explored the interactions of Zn-fertilizer, zinc-oxide nanoparticles (ZnO-NPs), and Zn-solubilizing Enterobacter cloacae (Zns-Ec) in mitigating Pb-induced phytotoxicity in 50, 100, and 150 mgPbkg−1 soil-stressed chickpea. Under Pb stress. Zn, ZnO-NP and Zns-Ec significantly (p < 0.05) improved root biomass (23.4, 52.3, and 71.4%), chl a (21.2, 26.5, and 39.8%), and carotenoids (26.7, 29.7 and 45.7%) in chickpea subjected to 50 mgPbkg−1 soil. Zn, ZnO-NP and Zns-Ec interactions reduced lipid peroxidation (LPO), hydrogen peroxide (H2O2) and membrane integrity and increased soluble proline, helping to mitigate oxidative stress in Pb-stressed chickpea. Zn, ZnO-NP and Zns-Ec increased antioxidant enzyme activity of chickpea with highest increases in catalase (CAT; 33.4, 40.7 and 51.2%), ascorbate peroxidase (APX; 24.5, 29.8, and 41.2%), glutathione reductase (GR; 20.7, 33.1 and 48.9%), peroxidase (POD; 24.8, 34.5, and 48.9%) under 150 mgPbkg−1 stress. Treatments of Zn, ZnO-NP and Zns-Ec greatly reduced Pb uptake in roots (20.1, 35.7, and 67%) and shoots (17.6, 29.5 and 54%), in 50 mgPbkg−1-stressed chickpeas. Additionally, Zn amendments significantly reduced Pb concentrations in rhizosphere soil, increased levels of available K and soluble P. Rhizosphere soil harvested from Zn, ZnO-NPs, and Zns-Ec treatments showed increased available P (8.2 24.5 and 29.5%) and K (24, 21, 34.5%) content under mgPbkg−1 Pb treatment. Zn, ZnO-NP, and Zns-Ec mitigated Pb toxicity in chickpea by enhancing antioxidant enzyme activity, reducing lipid peroxidation, and limiting Pb uptake through Zn–Pb interaction and rhizosphere immobilization. These findings the synergistic role of Zn amendments and metal-tolerant PGPR in improving plant resilience under heavy metal stress.